The impact of clock timing on VDT visual search performance under time constraint - Hu, Jiabin; Chen, Qun; Lu, Danqiong; He, Jingkang (Frontiers in Psychology, 2024)
Conducting Visual Display Terminal (VDT) visual search tasks under time constraint has broad applications in fields such as security checks, medical diagnostics, and rescue operations. Clock timing plays a crucial role in the visual interface, influencing the perception of time pressure and impacting visual search performance. To comprehensively investigate this impact, we conducted a pilot experiment to determine the content of the experimental tasks. The formal experiment was conducted in two phases over six sessions. Participants were tasked with locating the letter "E" embedded within the distractor letter "F," displayed with a clock area above the interface. The first phase of experiments included conditions of no clock, 4-minute clock timing, and 4-minute countdown clock timing. In the second phase of the experiment, the clock display method was a countdown clock, with three experiments conducted featuring long time, medium time, and short time. Utilizing search speed and accuracy as primary performance evaluation metrics, we examined the impact of clock timing methods and duration on visual search performance. Results from the first phase of experiments demonstrated that having a clock significantly increased the speed of visual search tasks compared to no clock displays, with not statistically significant in accuracy. Findings from the second phase of experiments indicated that shorter timing constraints led to faster search speeds but were accompanied by reduced accuracy and increased fatigue. Overall, a correlation exists between search speed and accuracy in visual tasks, where higher speed often correlates with lower accuracy. These research outcomes provide valuable insights into clock timing design for visual search interfaces under time pressure.